Online System on Monitoring and Feedback for Education - Sudirman, Sudirman (Universitas Trilogi, 2021)
This study reported the staging of process on developing a mobile application for real-time data management information system on monitoring and feedback in early childhood education, it can help tracking child care and education and assist teacher in monitoring and feedback on child services. A study was carried out to gather necessary information through data mapping, in-depth interviews with key stakeholders, document reviews, application development, direct entry in the field using mobile development, application testing and analysis that was conducted on for 253 respondents. To obtain a full picture on early childhood education, data on child growth and education shall be mapped and linked in one application. We introduce a mobile app to systematically compile the individual as well as group data across different aspects of child life, ranging from child education. Using a tablet PC or mobile phone, data could be easily entered at any time by the person. Due to still poor infrastructure at the grass root level, the system also allows a safety store offline that could automatically link to server when network connection is available. The immediate data entry will provide real-time data report that could be accessed by any relevant stakeholders at any levels to response accordingly. However, to avoid misuse of data, the access will also be restricted with a secured login system. Based on the study, this application is easily applicable for real-time monitoring and evaluation on early child education.